SYNERGETIC EFFECT - QUINTENCE OF INNOVATIVE DEVELOPMENT OF SOCIO-ECONOMIC SYSTEMS - Natalia, Alievskaya; Nadezhda, Belova; Inna, Geras'kina; Marina, Egorova (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the essence, content and conditions for the occurrence of synergistic effects in socio-economic systems. It is proved that the synergistic effect is the quintessence of the balanced innovative development of socio-economic systems. The most important forms of manifestation of synergetic effects are considered and analyzed: sustainable development, self-organization, phase transitions, system sensitivity, bifurcation, hysteresis, and emergence. Particular attention is paid to the process of self-organization in the context of spontaneous occurrence in the system of orderliness and new properties under the condition of insignificant control action. It is argued that the synergistic effect depends on the stage (stage of the cycle) of the development of the socio-economic system and the effectiveness of innovative management, and crises - a natural and regular stage of innovative development, where the platform of the next technological structure is laid. The question of society’s desire for economic growth is touched on, which, on the one hand, does not solve the various social and economic difficulties of mankind, and even contributes to the emergence of new problems (environmental, structural, etc.), which is justified by the law of compensation of entropy, and on the other hand, it can act as a fluctuating force in the evolutionary period, pushing the business entity to bifurcation. It is followed by a revolutionary and qualitative transformation of its structure. It is proved that the balanced innovative development of socio-economic systems is determined by such basic parameters as “degree of internal ordering” and “strength of external control action”. The essence and content of the synergetic potential of socio-economic systems are determined as their inherent property, formed through inter subject interactions and structural and institutional dynamics and providing sensitivity and an adequate response of the system to small exogenous and endogenous influences for its development according to a given vector of goals and indicators.